2013
DOI: 10.1016/j.chiabu.2012.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Placement decisions and disparities among Aboriginal children: Further analysis of the Canadian incidence study of reported child abuse and neglect part A: Comparisons of the 1998 and 2003 surveys

Abstract: Further analysis needs to be conducted to further understand individual and organizational level variables that may influence decisions regarding placement of Aboriginal children. There is also a need for research that is sensitive to differences among, and between, Métis, First Nations and Inuit communities. Results are not generalizable to Québec because data from this province were excluded.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 69 publications
(32 citation statements)
references
References 20 publications
1
30
0
1
Order By: Relevance
“…Within the small, but growing, body of research on the role of context in child maltreatment, a number of community variables have been found to be associated with maltreatment substantiations and foster care entry, including poverty (Coulton, Korbin, Su, & Chow, 1995; Freishtler, Bruce, & Needell, 2007; Freisthler, Midanik, & Gruenewald, 2004; Freisthler, Needell, & Guenewald, 2005; Fromm, 2004; Irwin, 2009; Lery, 2009), concentration of single, female-headed households (Coulton et al, 1995; Freisthler et al, 2007; Freisthler et al, 2004; Lery, 2009; Zhou, 2006), residential instability (Coulton et al, 1995; Freisthler et al, 2007; Freisthler et al, 2005; Fromm, 2004; Irwin, 2009; Lery, 2009), and concentration of minority children in investigations (Fallon, Chabot, Fluke, Blacstock, MacLaurin, & Tonmyr, 2013). These studies relied on neighborhoods as the geographical unit, whereas the current study focuses on counties.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Within the small, but growing, body of research on the role of context in child maltreatment, a number of community variables have been found to be associated with maltreatment substantiations and foster care entry, including poverty (Coulton, Korbin, Su, & Chow, 1995; Freishtler, Bruce, & Needell, 2007; Freisthler, Midanik, & Gruenewald, 2004; Freisthler, Needell, & Guenewald, 2005; Fromm, 2004; Irwin, 2009; Lery, 2009), concentration of single, female-headed households (Coulton et al, 1995; Freisthler et al, 2007; Freisthler et al, 2004; Lery, 2009; Zhou, 2006), residential instability (Coulton et al, 1995; Freisthler et al, 2007; Freisthler et al, 2005; Fromm, 2004; Irwin, 2009; Lery, 2009), and concentration of minority children in investigations (Fallon, Chabot, Fluke, Blacstock, MacLaurin, & Tonmyr, 2013). These studies relied on neighborhoods as the geographical unit, whereas the current study focuses on counties.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Police involvement in investigation 31 Opening for ongoing services 16 Opening for ongoing services 15 Opening for ongoing services 19 Opening for ongoing services 26 Opening for ongoing services [8][9][10][11]38 Opening for ongoing services [12][13][14][15]38 Opening for ongoing services 22 Retained Learning/developmental issues 20 Physical disability/health condition 20 Emotional/behavioural disorders 20 Internalizing disorders 6 Externalizing disorders 6 Presence of harm 6 Child functional impairment 8 …”
Section: Continued On the Following Pagementioning
confidence: 99%
“…Opening for ongoing services 16 Opening for ongoing services 15 Opening for ongoing services 19 Opening for ongoing services 26 Opening for ongoing services [8][9][10][11]38 Opening for ongoing services [12][13][14][15]38 Opening for ongoing services …”
Section: Maltreatment Characteristicsmentioning
confidence: 99%
“…The existing literature has also consistently found that earlychildhood adversities, such as neglect, emotional, physical, and sexual abuse, are risk factors for physical and mental health problems later in adulthood [21][22][23]. Most of these studies have shown higher rates of poor physical health [24][25][26], obesity [18], anxiety and depression [27], personality disorders [28], aggression and attention deficithyperactivity disorder (ADHD) [29], substance use disorders [30], chronic conditions [31], and suicide-related behaviors [32,33] among adults with a history of childhood adversities.…”
Section: Introductionmentioning
confidence: 99%